Climate change in your backyard: the role of local governments - Yookyung Lee; Jongjin Baik; Seungwoo Han (npj Urban Sustainability)
Abstract Local governments are central to climate governance, translating broad policy objectives into concrete actions. Unlike national debates, which are often polarized, municipal-level climate discourse is shaped by environmental stressors and governance imperatives. This study conducts a longitudinal analysis of local government climate discussions in South Korea, applying computational text and sentiment analysis to council meeting records. By integrating climate-related indices and political composition, this study examines how these conditions influence the discourse and sentiment of climate discussions. Results indicate a steady increase in climate discourse over time, with weather events serving as key catalysts. However, divisions in sentiment remain minimal, and the political composition of local councils does not significantly affect either the volume of discussions or sentiment divergence. These findings highlight the potential for depoliticized, pragmatic climate governance at the municipal level, providing insights into how local policymakers respond to climate challenges amid evolving environmental and political landscapes.